Manifestasies van die denke van Marx in die moderne kapitalisme: Bedryfs ekonomiese perspektief - Lessing, N. (Koers, 1985)
The author looks at manifestation of Marxism from the vantage point of business economics, and states that in looking at contemporary economic manifestations of Marxism it is meaningful to start with Marx's magnum opus. He offers a survey of various concepts from Das kapital, starting out with the observation that at present there is great confusion about the concepts capital, capitalist and capitalism. From a study of various definitions of capitalism he comes to certain conclusions, and states that Marx sees the crisis of capitalism in an "inherent fundamental contradicttion" of capitalism itself. He goes on to deal with the ideas of conscience as opposed to ecconomism, and subsequently states that the objective of Communism (modern and classical) is to subject the whole world to its power, in view of the fact that capitalism is seen as a transitory phase in the history of the development of mankind. He warns against the danger in many instances of replacing the words communist or socialist with the words capitalist or Calvinist, because this is symptomatic of the danger that Marxism in contemporary form is not always readily distinguishable as such.